Acute effects of flywheel eccentric overload on vertical jump, change of direction, and isometric mid-thigh pull performance in top-level team sports athletes - Andric, N.; Jezdimirovic-Stojanovic, T.; Mikic, M.; Mededovic, B.; Jakšic, D.; Stojanovic, M. D. M. (Sports, 2026)
We examined the acute effects of flywheel eccentric overload (FEO) on countermovement jumps (CMJs), changes of direction (COD), and isometric mid-thigh pulls (IMTPs) in top-level team sports athletes (three females and seven males). FEO was carried out by performing 3 × 6 reps with 0.025 kg·m2 inertia and a 2 min passive rest period. Its post-activation potentiation was compared to a control warm-up. Performance was tested at 0, 3, and 6 min post-intervention. Significant improvements were reported in the COD5m times for the left (F = 8.38, p < 0.001, ES = 1.92) and right legs (F = 11.3, p < 0.001, ES = 2.24), as well as for CMJ height (F = 12.4, p < 0.001, ES = 2.35). Significant differences were observed in COD5m between baseline and 3 min (p < 0.001, ES = 0.99 and p = 0.003, ES = 1.25) and 6 min (p = 0.04, ES = 1.19 and p < 0.001, ES = 1.09) for the left and right legs, respectively. Jump height increased significantly at 3 min (p < 0.001, ES = 1.62) and remained elevated at 6 min (p < 0.001, ES = 1.02). CMJ peak power (CMJPP) decreased significantly (F = 6.4, p = 0.002, ES = 1.68), with a drop at 0 min (p = 0.024, ES = 0.85) and a return to baseline at 3 min (p = 0.002, ES = 1.35). No significant effects were found for the CMJ eccentric rate of force development (CMJRFDecc) or IMTP. It was found that FEO can acutely enhance jumping and changes of direction but not strength in elite team sports athletes. A three-minute rest appears to maximize these effects.